Central Venous-to-Arterial CO2 Gap Is a Useful Parameter in Monitoring Hypovolemia-Caused Altered Oxygen Balance: Animal Study. (29th August 2013) - Kocsi, Szilvia; Demeter, Gabor; Erces, Daniel; Nagy, Eniko; Kaszaki, Jozsef; Molnar, Zsolt
Abstract : Monitoring hypovolemia is an everyday challenge in critical care, with no consensus on the best indicator or what is the clinically relevant level of hypovolemia. The aim of this experiment was to determine how central venous oxygen saturation (ScvO2 ) and central venous-to-arterial carbon dioxide difference (CO2 gap) reflect hypovolemia-caused changes in the balance of oxygen delivery and consumption. Anesthetized, ventilated Vietnamese minipigs (n = 10 ) were given a bolus followed by a continuous infusion of furosemide. At baseline and then in five stages hemodynamic, microcirculatory measurements and blood gas analysis were performed. Oxygen extraction increased significantly, which was accompanied by a significant drop in ScvO2 and a significant increase in CO2 gap. There was a significant negative correlation between oxygen extraction and ScvO2 and significant positive correlation between oxygen extraction and CO2 gap. Taking ScvO 2 < 73 % and CO2 gap >6 mmHg values together to predict an oxygen extraction >30%, the positive predictive value is 100%; negative predicted value is 72%. Microcirculatory parameters, capillary perfusion rate and red blood cell velocity, decreased significantly over time. Similar changes were not observed in the sham group. Our data suggest that ScvO 2 < 73 % and CO2 gap >6 mmHg can be complementary tools in detecting hypovolemia-caused imbalance of oxygen extraction.